Analisis dan Pemetaan Jumlah Penumpang Kereta Api di Indonesia Menggunakan Metode Statistik Deskriptif dan K-means Clustering: Analisis dan Pemetaan Jumlah Penumpang Kereta Api di Indonesia Menggunakan Metode Statistik Deskriptif dan K-means Clustering - Benny Wijaya; Tresna Maulana Fahrudin; Aryo Nugroho (Institute of Computer Science (IOCS), 2019)
The development of the population in Indonesia continues to increase, which will require more transportation facilities. PT. Kereta Api Indonesia (KAI) is one of the means of transportation in Indonesia. At present the railroad transportation facilities in Indonesia are still not comprehensive, the regions that have railroad transportation facilities are Java (Jabodetabek and outside Jabodetabek), and Sumatra. By taking data on the number of train passengers from the Central Statistics Agency (BPS), the analysis and mapping of the number of train passengers using descriptive statistics and K-means clustering was carried out in this study. This study produced 3 clusters in which each cluster has a measuring value. Cluster 0 is medium, cluster 1 is high, and cluster 2 is low. Calculated using k-means clustering produces a cluster of 0 there are 63, cluster 1 there is 47, and cluster 2 there are 46 with an accuracy of about 97.9%, and calculated using descriptive statistics to produce cluster 0 there are 108, cluster 1 there is 34, and cluster 2 exists 14 with an accuracy of about 93.6%